Pre-Service English Teachers’ Professional Identity and English Learning Self-Efficacy: Influences and Implications - Huang, Yanni (Journal of Research in Vocational Education, 2025)
This study examines pre-service English teachers’ professional identity and English learning self-efficacy within China’s post––course-competition–certificate framework. Survey data from 267 PESTs revealed a multidimensional structure of professional identity, including value, willingness and expectation, efficacy, and will. Professional identity was positively correlated with English learning self-efficacy, especially academic behavior and language-use efficacy. Voluntary choice of teacher education, competition participation, and award attainment predicted higher professional identity, while job priorities shaped professional will. The findings highlight the importance of competition-based mastery experiences and course–certificate alignment in enhancing PESTs’ learning confidence and professional growth, offering implications for optimizing vocational teacher education programs.